MODELING OF THE LOGISTICS SYSTEM OF THE ENTERPRISE IN THE CONDITIONS OF THE DIGITAL ECONOMY - ZHELIKHOVSKA, Maiia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In a globalized world characterized by technological changes, interactions between economic and social actors are crucial to exploit market opportunities and maximize resource efficiency. The digital transformation of the economy creates the prerequisites for the emergence of technological tools with fundamentally new properties, which are driven by the industrial implementation of artificial intelligence technologies, cloud computing and other innovative products. Production and logistics systems that support the life cycle of promising technical systems are also becoming active components of a single network of intelligent machines operating on the basis of Internet technologies. The problems of logistics remain relevant, because the successful functioning of any organization and its competitiveness directly depend on the competent interaction of all subsystems of the enterprise, including the logistics one. Organizations that cannot adapt to today’s information exchange and business process management requirements will find it harder to add value to their products and services. Digital transformation is a leading trend that reflects the development vector of the economy and society as a whole. The implementation of digital technologies in the logistics processes of the enterprise should be considered as an integral part of the development of the logistics system and the enterprise in general in modern conditions. The implementation of modern digital technologies in logistics activities leads to changes in business models and strategic planning; improves interaction between all participants of the logistics process; increases the productivity of activities and, as a result, increases the competitiveness of logistics enterprises in the market. In the conditions of rapid digitization, there is a need to master current delivery channels and formats, analyze big data, automate processes, implement blockchain and robots. The logistics industry is becoming one of the drivers of digitalization.